Violence against women and the level of seriousness of the situations. A comparison between the ENSIMUP and the Violentometer. Year 2023 (Revista Científica UCOM Scientia, 2024)
The article addresses the problem of violence against women in Paraguay, highlighting its increase despite current laws such as Law 5777/2016. In 2023, 40 femicides were recorded, exceeding the figures of previous years. The National Survey on the Situation of Women in Paraguay (ENSIMUP) reveals that almost 8 out of 10 women have experienced violence at some point in their lives, both in the private and public spheres.The research focuses on comparing the ENSIMUP data with the Violentometer, a tool that classifies the severity of violent situations into three levels: yellow (emotional/psychological), orange (economic/physical), and red (extreme violence, risk of feminicide). The study shows that 40% of the women surveyed have experienced situations of serious family violence, and 79% have suffered violence from their partners or ex-partners, with a predominance of serious and very serious cases.The article concludes that violence in the private-family sphere is on the rise, reflecting a deep problem in Paraguayan society that requires urgent attention from the authorities. The need to effectively implement public policies for the protection of women and overcome current barriers in reporting and seeking justice is pointed out.
Keywords: violentometer; violence against woman; Paraguay; ENSIMUP